2020
DOI: 10.1007/s11769-020-1161-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Structure, Hierarchy and Formation Mechanisms of Scientific Collaboration Networks: Evidence of the Belt and Road Regions

Abstract: Scientific collaboration has become an important part of the people-to-people exchanges in the Belt and Road initiative, and remarkable progress has been made since 2013. Taking the 65 countries along the Belt and Road (BRI countries) as the research areas and using collaborated Web of Science (WOS) core collection papers to construct an international scientific collaboration matrix, the paper explores the spatial structure, hierarchy and formation mechanisms of scientific collaboration networks of 65 countrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 55 publications
(66 reference statements)
0
9
0
Order By: Relevance
“…e calculation method to represent outgoing centrality and incoming centrality is shown in equation (2), where O(m) denotes the outgoing centrality of node m, I(m) denotes incoming centrality, 􏽐N mn denotes the number of nodes pointing to other nodes, and 􏽐N nm denotes the number of nodes accepting the number of other nodes.…”
Section: Research On Service Trade Indicators Of Countries Along the "Belt And Road"mentioning
confidence: 99%
See 1 more Smart Citation
“…e calculation method to represent outgoing centrality and incoming centrality is shown in equation (2), where O(m) denotes the outgoing centrality of node m, I(m) denotes incoming centrality, 􏽐N mn denotes the number of nodes pointing to other nodes, and 􏽐N nm denotes the number of nodes accepting the number of other nodes.…”
Section: Research On Service Trade Indicators Of Countries Along the "Belt And Road"mentioning
confidence: 99%
“…It will also promote the rapid development of the service industry. At this stage, the world economy is still in shock and slowly recovering, and cooperation among many regional organizations is still flourishing [2,3]. e "Belt and Road" project requires the use of multilateral cooperation mechanisms to promote the construction and sustainable development of the region.…”
Section: Introductionmentioning
confidence: 99%
“…At the end of the 20th century, the complex network theory based on mathematical graph theory and statistical physics provided a theoretical basis for studying the complexity of network systems [25][26][27]. Complex network theory and methods have been used in many fields such as disease transmission [28], transportation networks [29], scientific research cooperation networks [30], and urban networks [31,32]. is method also provides a new perspective for the identification of talent flow network structure.…”
Section: Space Of Flows Network and Talent Flowmentioning
confidence: 99%
“…where g jk is the number of shortest paths used to connect point j and point k and g jk (i) is the number of shortest paths through point i between point j and point k. [30].…”
Section: Betweenness Centralitymentioning
confidence: 99%
“…The above research has found that the high collinearity between the influence factors will have a certain impact on the GWR Model results. [63] In the results, we set the VIFs value to no more than 5 [64] for each factor. As shown in Table 5, only three meteorological factors-humidity, wind speed, and precipitation-passed the multicollinearity test.…”
Section: Analysis Of Meteorological Factorsmentioning
confidence: 99%